Calitatea mediului înconjurător în România și percepția populației - Chiriac, Dumitru; Pascal, Lăcrămioara Laura; Tatu, Mădălina (Calitatea Vieții, 1994)
The article presents the existing situation of the environment in Romania, completed by its perception within the population represented by the investigated subjects of an inquiry made by the Research Institute of the Quality of Life.